Setup errors and effectiveness of Optical Laser 3D Surface imaging system (Sentinel) in postoperative radiotherapy of breast cancer - Xiaobo Wei (Nature Portfolio, 2018)
Abstract Breast-conserving surgery (BCS) plus postoperative radiotherapy has become the standard treatment for early-stage breast cancer. The aim of this study was to compare the setup accuracy of optical surface imaging by the Sentinel system with cone-beam computerized tomography (CBCT) imaging currently used in our clinic for patients received BCS. Two optical surface scans were acquired before and immediately after couch movement correction. The correlation between the setup errors as determined by the initial optical surface scan and CBCT was analyzed. The deviation of the second optical surface scan from the reference planning CT was considered an estimate for the residual errors for the new method for patient setup correction. The consequences in terms for necessary planning target volume (PTV) margins for treatment sessions without setup correction applied. We analyzed 145 scans in 27 patients treated for early stage breast cancer. The setup errors of skin marker based patient alignment by optical surface scan and CBCT were correlated, and the residual setup errors as determined by the optical surface scan after couch movement correction were reduced. Optical surface imaging provides a convenient method for improving the setup accuracy for breast cancer patient without unnecessary imaging dose.